Bioavailability of astaxanthin in Haematococcus algal extract: The effects of timing of diet and smoking habits - Okada, Y.(Yamaha Motor Co., Ltd., Shizuoka (Japan)); Ishikura, M; Maoka, T (Bioscience, biotechnology, and biochemistry, 2009)
Astaxanthin is a caroteonid that possesses strong antioxidant activity. Recently, many studies on biological activity have been reported. In general, the absorption of carotenoids is affected greatly by diet and by smoking. In this report, we investigated astaxanthin pharmacokinetics after administration of Haematococcus algal extract, a source of astaxanthin, to smokers and nonsmokers before and after a meal; astaxanthin was given before the meal to nonsmokers (n=7), after the meal to nonsmokers (n=6), and after the meal to smokers (n=7), then serum samples were analyzed. The timing of administration greatly affected astaxanthin bioavailability including the area under the curve (AUC 0-168 , 2,968±959 μg h/l in the before-meal group vs. 7,219±3,118 μg h/l in the after-meal group), indicating high availability in the after-meal group. Smoking also affected the pharmacokinetic parameters and reduced the half-life (t 1⁄2 ) of astaxanthin elimination significantly.